Microsatellite repeats in common bean (Phaseolus vulgaris L.) : Isolation, characterization, and cross-species amplification in Phaseolus ssp - Gaitán Solís, Eliana; Duque E., Myriam Cristina; Edwards, K.J.; Tohme, Joseph M. (Wiley, 2002)
Phaseolus beans are distributed worldwide and are cultivated in the tropics, subtropics, and temperate zones. The common bean is the most important grain legume for direct human consumption in the world. The objectives of this study were to isolate microsatellite repeats and to establish their discriminatory power (DL) to be used in bean diversity characterization and mapping. We isolated, cloned, and sequenced genomic DNA fragments that contained microsatellite loci from three genomic libraries of Phaseolus vulgaris L. The polymorphism of the microsatellites was evaluated in a panel of 21 P. vulgaris genotypes made up of cultivated and wild beans from the Mesoamerican and Andean pools, and nine genotypes from four Phaseolus species. The number of alleles per microsatellite locus ranged from 1 to 14, with an average of 6 alleles per primer pair. Almost all the microsatellite loci showed high levels of discriminatory power, with the highest value being 0.94. These results indicate that microsatellites can be valuable genetic markers for assessing genetic diversity in the P. vulgaris The high levels of polymorphism of these new bean microsatellites and their wide cross-species transportability make these new markers useful for mapping and molecular characterization of Phaseolus species.